Development of a smart assistive stick for visually impaired people - Tor, Liqin (2023)
Visually impaired people are individuals who are unable to get their vision corrected to a 'normal level' or people who have difficulties to see objects clearly. They have constraints in carrying out their regular lives especially engaging in outdoor activities where they could get hurt unintentionally due to the inability to recognise obstacles. Iherefore, a smart stick is proposed in this project to assist them navigate their daily lives. This smart stick is integrated with multitude Of sensors, and its phone application development leverages Internet Of Things (IOT) technologies. In this project, the three objectives are: first is to evaluate the technically workability of each feature in the smart stick; second is to analyse the effectiveness of the smart stick in assisting and enhancing the safety of user; third is to evaluate the accuracy of live location tracking feature for the guardian to keep track of the location of visually impaired people. The microcontroller used in this project is ESP32. Three ultrasonic sensors are placed at different positions for obstacle detection. When one out of three of the ultrasonic sensors detects an obstacle within 50 cm in proximity, the buzzer will buzz immediately. A water sensor is also installed to identify the presence Of water, and the user will be alerted by a vibration produced from a motor. When the ultrasonic sensor detects the staircases, the phone application plays a corresponding audio alert via headphones. A mislocated stick can be found by pressing a button in the phone application, and the buzzer attached to the stick will respond. The user can then deactivate the buzzer by pressing designated button on the stick. The smart stick is also equipped with LED illumination feature, where it uses a LDR sensor to detect when the ambient light level is low and lights up its LEDs. There is emergency button installed in the stick to allow users to send SOS messages with their current location to their guardians through the phone application. Via the Ubidots dashboard, guardians can track the current location of the user. Based on results from the humanization test, the average walking speed Of participants equipped with the smart stick throughout the first and second tests was 0.17 mts. The average success rate Of smart stick users in avoiding obstacles is 92.5% and 91.11%, respectively. The test on water detection was recorded with 100% success rate among the 17 participants. All the participants were able to successfully send the SOS message with accurate location. In conclusion, the primary stage development Of the smart stick was proven a successful project with ample room for future development and improvement.